Нефтепереработка и нефтехимия: респ. межвед. сб. науч. тр. ([редкол.: В. Т. Скляр (отв. ред.) и др.]) - Скляр В. Т. (1991)
Экземпляры: КХ (20100513) / Инвентарный номер: 998776 / Цена: 3.20 / Сис.шифр: 35 / Авт.знак: Н 58 / ГРНТИ: 61 / ББК: 35.514